(untitled) (SCIENCE TIME JOURNAL, 2026)
The rapid evolution of artificial intelligence (AI) technologies has significantly transformed language learning, particularly in the domain of pronunciation training. This study examines the efficacy of AI-driven voice technologies in enhancing learners’ phonetic competence, emphasizing the integration of automated speech recognition (ASR), text-to-speech (TTS) systems, and real-time feedback mechanisms.